أثر استخدام الفيديو المتحرّك في ترقية مهارة الكلام لطلاب مدرسة خزانة كباجيكان المتوسطة الإسلامية تانجيرانج - Afiyah Nur Rusydah; Toto Edidarmo (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This research aims to examine the effect of using animated videos on students' speaking skills and to identify the supporting and inhibiting factors in teaching speaking skills through animated videos. The study employed a mixed-method approach that combines quantitative and qualitative research. The population in this study consisted of all seventh-grade students, with a research sample of 71 students divided into experimental and control groups. Data collection methods for the quantitative research included pre-tests and post-tests, while qualitative data were gathered through interviews and observations. Data analysis for the quantitative research employed t-tests. The results showed that the average post-test score for the experimental group was 81.6, compared to 72.4 for the control group. Data analysis using the Independent Sample T-test revealed a significant difference between the experimental and control groups, with a p-value of 0.000 (< 0.05), indicating that the alternative hypothesis was accepted and the null hypothesis was rejected. This demonstrates that the use of animated videos has a significant effect on speaking skills. Supporting factors in the learning process included increased student interest, support from the school environment, and ease of access to educational media. Inhibiting factors included differences in students' educational backgrounds and the need for additional time. This study explores the use of animated videos as a novel tool to improve intermediate-level Arabic speaking skills. It examines both the impact of these videos and the factors influencing the learning process. However, limitations include a small sample size limited to seventh-grade students and a short study duration, making it challenging to assess long-term effects.